Effects of Dietary Factors on Gastroesophageal Reflux Disease (GERD) Among the Student and Faculty of Public and Private Medical Universities of Karachi, Pakistan - Sobia Memon, Greesh Kumar Maheshwari, Sunnela Bhai, Areeb Ahmed, Umair Ahmed, Manal Amer Ali, Areesha Asad, Omayma Asif (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Gastroesophageal reflux disease (GERD) results from gastric contents moving into the esophagus, causing distressing symptoms and complications. Its prevalence has surged in the past two decades, notably in Asian countries. While nutritional management is common in clinical practice, definitive recommendations remain unclear. Few studies have explored the link between food and GERD. Methods: We conducted a descriptive cross-sectional study involving 359 eligible subjects out of 405 participants. We employed purposive sampling, targeting medical students, teachers, and staff aged 18 to 60 from four universities. Data were analyzed using SPSS version 26.0 with a confidence interval of 95% and a significance threshold of p < 0.05. Results: Among participants, 56.5% were female, with an average age of 24.55. Notably, 70.4% tested positive for GERD. Trigger foods included oily (24.2%) and spicy (45.4%) items, while 24.2% reported no specific triggers. Conclusion: This study underscores the significance of dietary modifications in managing GERD symptoms. Tailoring diets to individual symptoms and adjusting meal size, timing, and composition offer more benefits than elimination diets, particularly focusing on smaller meals and avoiding late-night eating habits. Keywords: Gastroesophageal reflux disease (GERD), reflux, esophageal disease, diet, nutrition, food intake, heartburn, fast-food.